Faktor - Faktor Yang Mempengaruhi Keteraturan Pemeriksaan Antenatal Care Pada Ibu Hamil Aterm: Factors Affecting Regularity of Antenatal Care Examinations for Pregnant Women at term - Erma Retnaningtyas; Candra Wahyuni; Retno Palupi Yonni Siwi; Shanty Natalia; Anggrawati Wulandari; Ersa Novani Kharisma Putri (Public Health and Safety International Journal, 2022)
The coverage of ANC visits in Indonesia in general is still low at 83.9% from the targeted 85% - 95%. Some of the factors that cause it include lack of knowledge, attitude, husband's support, distance and support from health workers. This study aims to determine the factors that affect the regularity of antenatal care in pregnant women at term. The research uses a cross-sectional correlation analytic design. The research population of all term pregnant women in Balongmojo Village, Puri District, Mojokerto Regency in March 2020 was 35 people. The number of samples is 31 respondents with purposive sampling technique. The research instrument used a husband's support questionnaire, a cadre role questionnaire, and a distance affordability questionnaire, and the regularity of ANC was measured using the MCH Handbook. Data analysis using Chi Square. The results of the study, most respondents received positive support from their husbands, namely 16 people (51.6%), most considered that the role of positive cadres was 17 people (54.8%), most of the distance from their homes were close to health care facilities, namely 17 people. (54.8%), and most of them perform ANC regularly, namely 18 people (58.1%). There is a relationship between Husband's Support (pvalue = 0.000), Role of Cadres (pvalue = 0.022, and Affordability (pvalue = 0.000) with ANC Regularity in Balongmojo Village, Puri District, Mojokerto Regency. Pregnant women are advised to perform ANC regularly from the beginning of pregnancy until before delivery so that maternal and fetal health is monitored.